Abnormal Trading Volume, Stock Returns and the Momentum Effects - ZHENG, Ying (Institutional Knowledge at Singapore Management University, 2007)
This paper intends to study the intermediate-term momentum and long-term reversal of stock prices by investigating the informational role of unusual trading volume for winner and loser stocks. I argue that unusual trading volume has different implications for winner and loser stocks. Specifically, high trading volume for losers is driven by purchases made by informed investors; while high trade volume for winners could be driven by either information or representativeness bias or both. The arguments are tested in the paper by showing that in the short run, losers/winners with high abnormal trading volume outperform losers/winners with low abnormal trading volume; while in the long run, the high-volume premium will be eliminated. Finally, I show that momentum profit is higher and more persistent among stocks with low abnormal trading since the loser with low volume bounces back slowly but winners with high volume fall faster and with greater magnitude.